2009
DOI: 10.1007/s10452-009-9304-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of temperature on biofilm formation in natural and modified marine environment

Abstract: Progression of biofilm formation was monitored at two stations near a nuclear power plant, Kalpakkam, located near coastal waters of Bay of Bengal. These stations are natural marine environment, station 1; and the condenser outfall area of the power plant the modified marine environment station 2. The biofilm formed on plexiglas panels was analysed in triplicates at 24 h intervals for various physical, chemical and biological parameters for 120 h (5 days). The biofilm formation showed both temporal and spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 40 publications
3
32
0
1
Order By: Relevance
“…Again, more work is needed to investigate the relative importance of these key biological processes in driving this pattern. The potential for oceanic warming to cause an increase in biofouling rates on artificial surfaces has been suggested previously, as microbial biofilm development may accelerate and aggressive fouling seasons may lengthen, particularly in temperate regions [16], [17]. Here, we observed greater fouling on warmer surfaces; an observation that could have major implications for the multi-billion dollar anti-fouling industry.…”
Section: Discussionsupporting
confidence: 70%
“…Again, more work is needed to investigate the relative importance of these key biological processes in driving this pattern. The potential for oceanic warming to cause an increase in biofouling rates on artificial surfaces has been suggested previously, as microbial biofilm development may accelerate and aggressive fouling seasons may lengthen, particularly in temperate regions [16], [17]. Here, we observed greater fouling on warmer surfaces; an observation that could have major implications for the multi-billion dollar anti-fouling industry.…”
Section: Discussionsupporting
confidence: 70%
“…The temperatures of treated sewage generally range from 10 to 35°C, so faster rates of biofouling are expected at higher temperatures. Rao and co-workers investigated both the effects of uniform temperature and water quality on biofouling, and reported such effects with changes in temperature (Rao 2010;Rao et al 2009). Likewise, Villanueva et al (2010) found that biofouling rate, biofilm thickness, enzyme activity, and the diversity of bacterial species in the biofilm all increased when the bulk temperature was raised from 7 to 11°C.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, the difference of water quality among groups was mainly due to the difference on microbial activities, which, in aquaculture, are present in planktonic phase and in the biofilm. The biofilm, with similarities to periphyton, is a ubiquitous organic matrix consisting of extra polymeric substances, bacteria and periphytic algae that coevolves with their planktonic cells during conditions with nutrient load (Rao, 2010;van Dam et al, 2002). In the present study having tanks with a relatively short retention time of 9 h, the planktonic cells were constantly diluted by the flow-through design.…”
Section: Impact Of Paa Application On Water Quality and Biofilm Formamentioning
confidence: 99%